Quench beat fatigue, drop weight, and heal your body through the new science of optimum hydration - Cohen, Dana; Bria, Gina (New York Hachette Books, 2018)
"Chronic headaches...brain fog...fatigue...weight gain...insomnia...gut pain...autoimmune conditions. We may think these and other all-too-common modern maladies are due to gluten intake or too much sugar or too little exercise. But there is another missing piece to the health puzzle: Proper hydration. Yes, even in this era of Poland Spring many of us are dehydrated due to moisture lacking diets, artificial environments, medications, and over-dependence on water as our only source of hydration. For this reason, that new diet or exercise plan may fail because our body doesn't have enough moisture to support it. Quench presents a wellness routine that can reverse all of that, based on breakthrough new science in the field of hydration. Readers will be surprised to learn that drinking too much water can flush out vital nutrients and electrolytes. Here is where "gel water" comes in: the water from plants (like cucumber, berries, aloe), which our bodies are designed to truly absorb right down to the cellular level. In fact, Ms. Bria's work as an anthropologist led her to the realization that desert people stay hydrated almost exclusively from what they eat, including gel plants like cactus. Based on groundbreaking science from the University of Washington's Pollack Water Lab and other research, Quench offers a five-day jump start plan: hydrating meal plans and the heart of the program, smoothies and elixirs using the most hydrating and nutrient-packed plants. Another unique feature of their approach is micro-movements-small, simple movements you can make a few times a day that will move water through your fascia, the connective tissue responsible for hydrating our bodies. You will experience more energy, focus, and better digestion within five days...then move onto the lifetime plan for continued improvements, even elimination of symptoms"--Provided by publisher.
"Based on breakthrough new science in the field of hydration, QUENCH debunks many popular myths about "getting enough water" and offers a revolutionary five-day jump start plan that shows how better hydration can reduce or eliminate ailments like chronic headaches, weight gain, gut pain, and even autoimmune conditions"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Nutrition; Hydration; Food habits